Working for Justice: The L.A. Model of Organizing and Advocacy - McCartin, Joseph A. (Labour / Le Travail, 2011)
The article reviews the book ,"Working for Justice: The L.A. Model of Organizing and Advocacy," edited by Ruth Milkman, Joshua Bloom, and Victor Narro.
Keywords: BLOOM, Joshua; BOOKS -- Reviews; Labor movement; MILKMAN, Ruth; NARRO, Victor; Nonfiction; United States; WORKING for Justice: The LA Model of Organizing & Advocacy (Book)